The Effectiveness of Local Plants Katuk Leaves and Papaya Leaves as Galactagogues in Increasing Breast Milk Production at TPMB Badriah Susilawati in 2022 - Nofi Herawati; Nursitiyaroh Nursitiyaroh (International Journal of Health and Pharmaceutical (IJHP), 2023)
Background: The main source of food and nutrition for newborns is breast milk (ASI). The nutrients that newborns need to meet their nutritional needs during the first six months of life are found in breast milk. Purpose of Writing: to find out the Effectiveness of Local Plants Katuk Leaves and Papaya Leaves as Galactagogues in Increasing Breast Milk Production at TPMB Badriah Susilawati in 2022. Research Methods: The research methodology used in this research is a quasy experimental research design used is a Nonequivalent Control Group Design with a quantitative approach. Researchers wanted to know the effectiveness of local plants katuk leaves and papaya leaves as a galactagogue to increase breast milk production. Research Results: Independent statistical test results sample t test value Sig. (2-tailed) namely 0.189 which is 0.189 > 0.05, so it can be concluded that there is no difference between giving katuk leaves and papaya leaves to increase milk production so that there is a similarity in the effectiveness of loka katuk leaves and papaya leaves as a galattagogue for increasing milk production in TPMB Badriah Susilawati Year 2022 Conclusions and Suggestions: The results of this study are expected to be a guide for female students who are interested in learning more about how to increase milk production by consuming foods that act as galactagogues, especially papaya and katuk leaves.